Субъектное начало теоретизирования в феноменологической социологии - Щербина, В. (Социология: теория, методы, маркетинг, 2000)
In the context of phenomenological sociology scientific objectivity is the consequence of interaction of a sociologist as an individual and sociological community as a whole. This phenomenological attitude doesn’t essentially differentiate between theoretical and common-sense mental activity and brings social theorizing down to “epiphenomenon”, i.e. to ideology which is understood as constructing social realities and values. Thus, social science is supposed to response to the demands of bearers of certain interests suggested by the existing social conditions.